JURIDICAL ANALYSIS OF THE RIGHT OF INQUIRY OF THE HOUSE OF REPRESENTATIVES IN PERFORMING THE SUPERVISORY FUNCTION ACCORDING TO INDONESIAN CONSTITUTIONAL LAW - Riastri Haryani; Sumiyanto, Oki (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The right of inquiry of the House of Representatives is a right to conduct an investigation owned by the House of Representatives that decides that the implementation of a law in government policies that is important, strategic, and has a wide impact on community life, the nation, and the state is allegedly contrary to legislation. The right of inquiry of the House relating to the exercise of the supervisory functions of the House is “an institutionalized system, involving the effectiveness and regularity of restrictions on government actions. In Indonesian constitutional practice, the right of inquiry is rarely implemented. Twice executed during the reign of the old order and twice executed during the reign of the new order. The use of the right of inquiry in the current presidential system shows a significant increase. This study uses normative juridical methods that are descriptive and analytical. Basically, the right of inquiry is a constitutional right of the DPR in the constitutional system as part of carrying out the function of supervision and balance of the executive. As a result of the legal application of the right of inquiry, the House of Representatives can exercise the right to express an opinion.